Effect of Alum Additions to Poultry Litter on In‐House Ammonia and Greenhouse Gas Concentrations and Emissions. Issue 5 (1st September 2015) - Eugene, Branly; Moore, Philip A.; Li, Hong; Miles, Dana; Trabue, Steven; Burns, Robert; Buser, Michael
Abstract : Alum [Al2 (SO4)3 ·14H2 O] addition to poultry litter has been shown to reduce ammonia (NH3 ) concentrations in poultry houses; however, its effects on greenhouse gas (GHG; N2 O, CH4, and CO2 ) emissions is unknown. The objectives of this study were to determine the effects of alum additions on (i) in‐house NH3 and GHG concentrations, (ii) NH3 and GHG emissions, and (iii) litter chemical properties. Two identical broiler houses located in northwest Arkansas were used for this study: one house was a control and the other was treated with alum between each flock of birds. Ventilation rates were coupled with in‐house NH3 and GHG measurements to determine emission rates. Overall, alum additions significantly reduced the daily average in‐house NH3 concentration by 42% (8.9 vs. 15.4 μL L −1 ), and the overall NH3 emission rate was reduced by 47% (7.2 vs. 13.4 kg d −1 house −1 ). The average cumulative NH3 emission for the three flocks was 330 kg house −1 flock −1 for the alum‐treated house and 617 kg house −1 flock −1 for the control. Concentrations and emissions of nitrous oxide (N2 O) and methane (CH4 ) from the alum‐treated house were not significantly different than the untreated house. However, carbon dioxide (CO2 ) emissions were significantly higher from the untreated house than the alum‐treated house. Alum also significantly increased litter N content and reduced the C/N ratio. These results indicate that the addition of alum to poultry litter is not only an effective management practice for reducing in‐house NH3 concentrations and emissions but also significantly reduces CO2 emissions from poultry facilities. Core Ideas: Alum additions did affect NH3 concentrations in poultry houses. Alum additions did affect NH3 emissions from poultry houses. Alum additions did affect CO2 emissions from poultry houses. Alum additions did not affect N2 O and CH4 emissions from poultry houses.